The Egyptian Society in Shamsuddin Bbn Danial Al-Moosely Al-Kahhal's Poetry - Taghreed Waddah Mustafa Koni (My University, 2013)
This research discusses the Egyptian society in the poetry of Shams Al-Din Ibn Daniyal Al-Mawsili Al-Kahhal (631-711 Hijri), and is considered part of the many of parts of the literary research that focuses on the history of the Arabic literature. It reveals the details of the Egyptian society in the Mamluki era through the poetry of Ibn Daniyal. Ibn Daniyal Al-Mawsili is considered among the most popular and most famous poets of the first Mamluki era. He was the poet of the society, and dedicated his poetry to his society and its characteristics, the different events that took place as well as the sufferings that it had. The poet had shaped his style of expression and mixed it with his vivacious soul, and although the society had been extensively addressed in his poetry, there is no extensive and independent scientific study that addresses the society from all of its different aspects. Therefore, this research came to focus on this aspect and to try to study society in Ibn Daniyal’s poetry, in addition to discussing the poetic characteristics in his poems. The researcher used the Analytical, Descriptive and Aesthetic Approach, and divided the study into an introduction, four chapters and a conclusion. In the first chapter, the researcher addressed the translation of the life of Ibn Daniyal Al-Mawsili Al-Kahhal, while in the second chapter he talked about the poet’s suffering in particular and the society in general. He explained poverty, its reasons and results in Ibn Daniyal’s poetry. In the third chapter, the researcher discussed the positive and negative civilization aspects that reflected the nature of life back in that time. In the fourth chapter, the researcher focused on discussing the structure of the poem, the poet’s language, methods, artistic styles and the artistic imagery in his poetry. Finally, the conclusion included the main results that this research has accomplished.

يتناول هذا البحث موضوع" المجتمع المصري في شعر شمس الدّين ابن دانيال الموصليّ الكحّال (631- 711هـ)". وتعدّ هذه الدّراسة حلقة من حلقات البحث الأدبيّ في تاريخ الآداب العربيّة، وقد جاءت لتكشف النّقاب عن تفاصيل المجتمع المصريّ في العصر المملوكيّ من خلال شعر ابن دانيال. يعد ابن دانيال الموصليّ من الشعراء المشهورين في العصر المملوكيّ الأوّل، هو شاعر من شعراء المجتمع، سخّر معظم شعره في الحديث عن مجتمعه وخصائصه، وما كان يدور فيه من أحداث ومعاناة، وقد اصطنع الشّاعر أسلوبه الخاصّ في التّعبير ومزجه بروحه المرحة، وعلى الرّغم من حضور المجتمع في شعره إلاّ أنّه لا توجد دراسة علميّة مستقلّة موسّعة تتناوله من جوانبه المختلفة، ومن هنا جاء البحث ليقف عند المجتمع في شعره، ثم ليبيّن خصائص شعره الفنيّة. واعتمد البحث المنهج التّكامليّ؛ وانتظم عقده في مقدمة وأربعة فصول وخاتمة: الفصل الأول؛ تناول ترجمة حياة الشاعر ابن دانيال الموصلي الكحّال. الفصل الثاني؛ تحدث عن معاناة الشاعر بخاصة والمجتمع بعامة؛ فوقف على تجليات الفقر وأسبابه في شعر ابن دانيال، ونتائجه. الفصل الثالث؛ وقف عند المظاهر الحضارية الإيجابية والسلبية التي عكست طبيعة الحياة في ذلك العصر. أمّا الفصل الرابع؛ فتحدّث عن بناء القصيدة عند الشاعر، وعن لغته وأساليبه، والفنون البديعية، والصورة الفنيّة في شعره. وأخيراً تأتي خاتمة البحث حاملة النتائج المستخلصة من هذه الدراسة.
المجتمع المصري في شعر شمس الدين ابن دانيال الموصلي الكحال